Role of flower-like ultrathin Co3O4 nanosheets in water splitting and non-aqueous Li–O2 batteries. Issue 21 (23rd May 2018) - Wu, Haitao; Sun, Wang; Shen, Junrong; Rooney, David W.; Wang, Zhenhua; Sun, Kening
Abstract : The bifunctional Co3 O4 nanosheets catalyst in aqueous system promotes the decomposition of DMSO-based electrolyte, resulting in spurious Li–O2 batteries performance. Abstract : The oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) are both fundamental and essential processes for various energy conversion and storage systems. The kinetics of ORR and OER play a critical role in their energy efficiency and practicality. Here, flower-like ultrathin Co3 O4 nanosheets synthesized through a facile solvothermal technique were studied as a bifunctional catalyst for both water splitting and non-aqueous Li–O2 batteries. Due to the novel structure and highly active 110 and 100 exposed facets, which can effectively facilitate mass transfer and enhance catalytic capability, Co3 O4 nanosheets exhibit better stability and higher ORR/OER activity than Co3 O4 nanoparticles, Co3 O4 bulks, Pt/C, and RuO2 in alkaline solution. More importantly, Li–O2 batteries with ultrathin Co3 O4 nanosheets catalyst can enhance the initial discharge capacity from 6400 to 8600 mA h g −1 and improve the cyclability up to 160 cycles at 500 mA g −1 . Unexpectedly, XRD and UV/Vis techniques suggest that the main product in Co3 O4 nanosheets based cathodes is LiOH, with resulting LiOH also demonstrating reversible formation/decomposition behavior, rather than Li2 O2 in pure Super P based cathodes. Further investigation confirms that Co3 O4 can also catalyze the electrolyte decomposition responsible for the formation of LiOH, and a reaction mechanism was illustrated. This work highlights that the traditional high-efficiency bifunctional catalyst in aqueous media may not be suitable for non-aqueous Li–O2 batteries, and the effect of catalyst on electrolyte besides the discharge product should also be carefully considered for the design of more stable and practical Li–O2 systems.